Exploring the role of metabolomics in kidney transplantation: a systematic review of the literature - Băluţă, Cezar Valeriu; Voroneanu, Luminiţa; Nistor, Ionuţ; Siriteanu, Lucian; Covic, Andreea Simona; Irimie-Băluţă, Raluca Erika; Kanbay, Mehmet; Miron, Adelina Vasilica; Covic, Adrian Constantin (Frontiers in Immunology, 2025)
BackgroundSerum creatinine and proteinuria remain the most frequently used test for monitoring allograft function. However, they are non-specific and insensitive markers. Metabolomics is an emerging field, dealing with the high-throughput identification and quantification of small molecules metabolites. We aimed to systematically review all available data regarding kidney transplantation and metabolomics.MethodsThis is a systematic review evaluating metabolomic usage in kidney transplant patients. A comprehensive search was assembled in the time span extending from inception until March 2024 across MEDLINE (PubMed), Embase and Cochrane. In addition to the databases above, eligible citation were sought through the screening of ClinicalTrials.gov and Google Scholar. Two authors assessed potential citations for eligibility and quality and extracted all data.ResultsA total of 57 articles were identified for inclusion (totaling 3821 patients), containing different methodologies and outcomes related to metabolic profiling. We aimed to offer support for finding new biomarkers that could aid in the evaluation of the kidney transplant patient, covering pathophysiological mechanisms and exploring avenues for personalized care.ConclussionOur systematic review underlines the possible role of metabolomics in monitoring kidney transplant patients. By integrating data from numerous studies, we have detected possible new biomarkers that might transform the method we screen kidney transplant recipients.